2008
DOI: 10.1038/npp.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thalamus–Hypothalamus Serotonin Transporter Availability during Clomipramine Administration in Patients with Obsessive–Compulsive Disorder

Abstract: To the authors' knowledge there is as of yet no study demonstrating in vivo alterations in human serotonin transporters (SERT) during clomipramine treatment in patients with obsessive-compulsive disorder. The only study in which SERT binding has been investigated in obsessive-compulsive disorder (OCD) patients before and after treatment is a small pilot study by Stengler-Wenzke et al (2006), who treated five OCD patients with citalopram. In the study at hand, we measured transporter availability in the thalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…However, validation of this ex vivo method (in cultured cells) with concomitant in vivo SPECT or PET SERT occupancy (the gold standard) is not yet available. In addition, Zitterl et al (2008) found a significant relation between SERT occupancy and clinical response in obsessivecompulsive disorder treated with clomipramine (150 mg per day), but did not study the effects of dose escalation in their study. Therefore, our study optimally quantifies the neurobiological effects of dose escalation of antidepressants in patients.…”
Section: Neurobiological Effects Of Dose Escalationmentioning
confidence: 92%
“…However, validation of this ex vivo method (in cultured cells) with concomitant in vivo SPECT or PET SERT occupancy (the gold standard) is not yet available. In addition, Zitterl et al (2008) found a significant relation between SERT occupancy and clinical response in obsessivecompulsive disorder treated with clomipramine (150 mg per day), but did not study the effects of dose escalation in their study. Therefore, our study optimally quantifies the neurobiological effects of dose escalation of antidepressants in patients.…”
Section: Neurobiological Effects Of Dose Escalationmentioning
confidence: 92%
“…In contrast, Zitterl et al (28) reported a negative association between OCD symptom severity and thalamic/hypothalamic serotonin transporter availability in both the baseline and post-treatment conditions. Given the hyperactive pattern in the limbic and paralimbic regions, the inverse relationship between changes of thalamic activity and OC symptom severity may be a compensatory mechanism for unfulfilled improvement of OC symptoms or a overloaded result in the frontal-striatal circuit (7).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, high stereotypy in deer mice correlates to reduced striatal serotonin transporter (SERT) density (Wolmarans et al, 2013), a recognized pathological feature of OCD (Zitterl et al, 2008), whereas SERT is also the preferential target for SSRIs (El Mansari & Blier, 2006). In this study, we challenged H animals with MB in order to screen for anxiety (neophobia) and compulsivity and to determine the response of said behavior to chronic escitalopram treatment, a known anxiety and OCD treatment modality.…”
Section: Discussionmentioning
confidence: 99%